THE ROLE OF STAKEHOLDER IN BUILDING A BRAND IMAGE AT MADRASAH ALIYAH - Fajri Dwiyama; Nurhasanah R (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Brand image is a representation of the overall perception of a brand and is formed from information and knowledge of that brand. Having a positive brand image for educational institutions in today's global competition is very important. The existence of a brand image is an alternative in winning the education marketing competition. A positive brand image is formed from the continuous role of various elements of stakeholders in educational institutions. Madrasah Aliyah Al-Ikhlas Ujung Bone is one of the private educational institutions established in the pesantren environment, which has a very good brand image. The indicator appears from the high public interest in these educational institutions. Even though they have a brand image, there is no visible role of school residents in building this brand image. This is the reason behind this research. The type of research used is qualitative research, data collection methods in the form of observation, interviews and documentation. Data analysis techniques are data reduction, data display, and drawing conclusions. The results of the study were related to the role of school members in building image bran, namely: 1) the characteristics of the brand image in Madrasah Aliyah Al-Ikhlas Ujung Bone, namely the existence of a strong image of the maker, the image of the user and the image of production. 2) the role of school members in building brand image, namely forming perceptions, maintaining perceptions, and changing perceptions.